Phenotypic variability within the desminopathies: A case series of three patients - Yeow, Dennis; Katz, Matthew; Henderson, Robert; Prasad, Sandhir; Denman, Russell; Blum, Stefan; Davis, Mark; Robertson, Thomas; McCombe, Pamela (Frontiers in Neurology, 2023)
Desmin is a skeletal and cardiac muscle intermediate filament encoded by the DES gene. Pathogenic variants in DES produce a range of skeletal and cardiac muscles disorders collectively known as the desminopathies. We report three desminopathy cases which highlight the phenotypic heterogeneity of this disorder and discuss various factors that may contribute to the clinical differences seen between patients with different desmin variants and also between family members with the same variant.